SHORES ROBUSTA GAERTN.F. (SAL) IN THE FORESTRY OF NEPAL - Rautiainen, Olavi; Suoheimo, Jouni (วารสารวนศาสตร์ไทย, 2022)
The distribution, silvicultural characteristics, growth rate and economic importance of S robusta Gaertn.f., an indigenous hardwood species in Nepal, were analysed. The natural S robusta forests in the southern plains of Nepal (the Bhabar-Terai) have been seriously degraded during the past decades. Forest inventories and trials in Nepal have revealed a good regeneration potential for the existing S robusta forests. After regeneration felling the new S. robusta crop reaches a standing stem volume of 100 m3 ha-1 in ten years. With an average site quality of 1/11, the maximum mean annual increment of stemwood (15 m3 year-1) is reached after 25 years and the maximum sawlog size wood MAL (5.7 m3 year-1. 20 cm top, under bark) after 60 - 70 years. The productivity of the dense naturally regenerated young forests is on a par with the commonly planted species in Nepal. Keywords: Shorea robusta Gaertn.f., sal, Nepal, silviculture, growth, forest management